The Legal Framework Governing Merger Transactions in Tunisia: A Comparative Analysis of Equitable Competition with France - Bhouri, Habiba (Journal of Ecohumanism, 2024)
This abstract offers an in-depth comparative analysis of the legal frameworks governing merger operations in the Tunisian Republic and the French Republic, highlighting the legal and regulatory mechanisms aimed at guaranteeing fair competition on the markets. The study explores in detail the similarities and distinctions between these two legal systems, looking at key aspects such as the notification procedures for mergers and acquisitions, the essential criteria for assessing merger operations, as well as the sanctions imposed in the event of proven anti-competitive practices. This comparative analysis provides essential legal perspectives to understand the different approaches taken by these two nations to the regulation of merger operations, thereby contributing to an in-depth understanding of the practices and legal obligations surrounding these transactions in an international context.